APPEARANCE OF SOCIAL PHOBIA IN ADOLESCENCE AND ITS NEGATIVE CONSEQUENCES - Usmonov Sherzod Axmadjonovich; Abdullayeva Muslimaxon Muzaffarxon qizi (Journals Park Publishing, 2022)
The article describes the manifestation of social phobia in adolescence and its negative consequences, these factors are empirically researched, psychological analysis is given, conclusions and recommendations are developed based on the results.
Keywords: fear, social phobia, anxiety, communication, introversion, shyness, excitability, self-awareness